Lack of delayed neurocognitive side effects of Gamma Knife radiosurgery in acromegaly: the Later-Ac study. Issue 1 (30th November 2021) - Castinetti, Frederic; Caron, Philippe; Raingeard, Isabelle; Amodru, Vincent; Albarel, Frederique; Morange, Isabelle; Chanson, Philippe; Calvo, Julie; Graillon, Thomas; Baumstarck, Karine; Dufour, Henry; Regis, Jean; et al.
Abstract: Introduction: Persistent growth hormone hypersecretion can be observed in roughly 50% of patients operated for somatotroph adenomas, requiring additional treatments. Despite its proven antisecretory efficacy, the use of Gamma Knife radiosurgery (GK) is limited probably due to the lack of data on long-term side effects, including potential cognitive consequences. Methods: The LATe Effects of Radiosurgery in Acromegaly study was a cross-sectional exposed/unexposed non-randomized study. The primary objective was to determine the long-term neurocognitive effects of GK focusing on memory, executive functions, and calculation ability. Exposed patients had been treated by GK for acromegaly at least 5 years before inclusion. Unexposed patients (paired for age) had to be cured or controlled at last follow-up without any radiation technique. Patients of both groups were cured or controlled at the last follow-up. Results: Sixty-four patients were evaluated (27 exposed and 37 unexposed). Mean follow-up after GK was 13 ± 6 years (including 24 patients followed for at least 10 years). While up to 23.8% of the patients of the whole cohort presented at least one abnormal cognitive test, we did not observe any significant difference in neurocognitive function between both groups. During the follow-up, 11 patients presented at least one new pituitary deficiency ( P   = 0.009 for thyroid-stimulating hormone deficiency with a higher rate in exposed patients), two presented a stroke (1 in each group), and one presented a meningioma (12 years after GK). Conclusions: While GK exposes patients to a well-known risk of pituitary deficiency, it does not seem to induce long-term cognitive consequences in patients treated for acromegaly.